علاقة الفقه بالنحو وتخريج بعض الفروع الفقهية على أصول نحوية - بن خدة سي محمد (University of Eloued جامعة الوادي, 2023)
لقد أنزل الله تعالى القرآن الكريم بلسان عربي مبين، فلا شك عندئذ أن فهمه ـ وكذا السنة ـ يحتاج للعلم باللغة العربية بعلومها، وهذا يدل على مدى حلقة التواصل بين علوم الشرعية عموما وعلم العربية، ويتلخّص هذا البحث في بيان لون من ألوان الاتصال، وحلقة من حلقات التفاعل بين الفقه والنحو ببيان وجه ذلك ومداه، وبإيراد كلام أهل العلم، مع التمثيل لهذا التفاعل بأمثلة فقهية تجسّد هذا التفاعل، وتظهر هذه الحلقة التفاعلية، وذكر مثال على أصل نحوي تتخرّج عليه فروع فقهية. Abstract : ALLAH HAS REVEALED QURAN IN A CLEAR ARABIC TONGUE, SO THERE IS NO DOUBT AT THAT TIME THAT UNDERSTANDING IT -AS WELL AS THE SUNNAH - REQUIRES KNOWLEDGE OF THE ARABIC LANGUAGE WITH ITS SCIENCES, AND THIS INDICATES THE EXTENT OF THE LINK BETWEEN THE SCIENCE OF SHARIA IN GENERAL AND THE SCIENCE OF ARABIC, AND THIS RESEARCH IS SUMMARIZED IN EXPLAINING ONE OF THE COLORS OF COMMUNICATION, AND ONE OF THIS THE INTERACTION BETWEEN JURISPRUDENCE AND GRAMMAR BY EXPLAINING THE FACE AND EXTENT OF THIS, AND BY CITING THE WORDS OF THE SCHOLARS, WITH REPRESENTATION OF THIS INTERACTION WITH JURISPRUDENTIAL EXAMPLES THAT EMBODY THIS INTERACTION, AND THIS INTERACTIVE EPISODE APPEARS, AND HE MENTIONED AN EXEMPLE OF A GRAMMATICAL ORIGIN ON WHICH JURISPRUDENTIAL BRANCHES GRADUATE
Keywords: الفقه ؛ النحو ؛ العلاقة ؛ الفروع الفقهية ؛ التخريج; Jurisprudence; grammar; relationship; legal branches; derivation.